Targeting microglia–oligodendrocyte crosstalk in neurodegenerative and psychiatric disorders. Issue 9 (September 2022) - Rahimian, Reza; Perlman, Kelly; Canonne, Candice; Mechawar, Naguib
Highlights: Microglia are resident macrophages of CNS that are involved in brain homeostasis. Oligodendrocytes are myelinating cells of the CNS that metabolically support axons. Microglia-oligodendroglia crosstalk is important in both health and disease. Predicted ligand-receptor interactions are dysregulated in MS and MDD. Ligand-receptor interactions between microglia and oligodendroglia are druggable. Abstract : To understand how various brain cell types communicate with each other to orchestrate functional processes, it is crucial to comprehend the signals used to relay such information. Therefore, an important challenge to studying complex brain diseases is to interrogate relevant interactions between cell types. The microglia–oligodendroglia interaction is an important example that has fundamental roles in physiological state and brain pathologies. Here, we review the latest findings on microglia–oligodendroglia interplay in physiological and pathological conditions. Furthermore, we provide an in silico ligand–receptor interaction analysis to explore potential druggable targets in multiple sclerosis (MS) and major depressive disorder (MDD).